On vector bundles for a Morse decomposition of $L\mathbb{C}P^n$ - Ottosen, Iver (MATHEMATICA SCANDINAVICA, 2017)
We give a description of the negative bundles for the energy integral on the free loop space $L\mathbb{C}P^n$ in terms of circle vector bundles over projective Stiefel manifolds. We compute the mod $p$ Chern classes of the associated homotopy orbit bundles.